2020
DOI: 10.3390/molecules25051063
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanoparticles Stimulates Spermatogenesis Impairments and Hematological Alterations in Testis and Epididymis of Male Rats

Abstract: The potential pharmaceutical application of nanoparticles has led to the toxicity within the male reproductive system. In the present study, the effects of silver nanoparticles (Ag-NPs) on hematological parameters, free radical generation, antioxidant system, sperm parameters, and organ histo-morphometry in male rats were investigated. Ag-NPs were produced by the reduction of silver ions, while the formation of which was monitored by UV–visible spectrophotometry. Zeta potential, transmission, and scanning elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
31
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 53 publications
8
31
2
Order By: Relevance
“…A considerable decrement in the relative weight of epididymis and BW of mice receiving a high dose of SWCNT (50 mg/kg) for 35 days is an indication of induced epididymal atrophy. In line with our observations, Olugbodi et al (77) and Watanabe (78) reported reductions in the relative weight of epididymis and testes (after 7 days) and vesicular and prostate glands (after 19 days) following nanoparticle administration to rats. We found the toxic effects of high CNTs doses on body weight and epididymal weight.…”
Section: Discussionsupporting
confidence: 92%
“…A considerable decrement in the relative weight of epididymis and BW of mice receiving a high dose of SWCNT (50 mg/kg) for 35 days is an indication of induced epididymal atrophy. In line with our observations, Olugbodi et al (77) and Watanabe (78) reported reductions in the relative weight of epididymis and testes (after 7 days) and vesicular and prostate glands (after 19 days) following nanoparticle administration to rats. We found the toxic effects of high CNTs doses on body weight and epididymal weight.…”
Section: Discussionsupporting
confidence: 92%
“…OH). 70,71 However, inadequacy in antioxidant systems to scavenge ROS has been implicated in the onset of dysgonadogenesis. 7,59 In this study, we observed that the animals treated with DOX exhibited a marked (p < 0.05) diminution in the activities of antioxidant enzymes such as SOD, CAT, GPx, GST, as well as non-enzymatic antioxidants including GSH and TSH, similar to other reports.…”
Section: Discussionmentioning
confidence: 99%
“…NPs are used for dermatological treatments, for skin care and in diagnostic imaging of skin diseases [ 64 ]. Sub-dermal exposure of Ag NPs for 7 and 28 days in male rats showed alterations in sperm number and motility as well as in testosterone (T), luteinizing hormone (LH) and follicle-stimulating hormone (FSH) levels along with histological abnormalities in the testis [ 65 ]. In some studies, it is reported that NPs cannot penetrate the skin, while in others penetration of metallic NPs, including iron NPs, is confirmed through hair follicles [ 66 ].…”
Section: Path Of Nps Into the Reproductive Systemmentioning
confidence: 99%
“…A very recent study demonstrated that nanosized Ag NPs caused toxic effects on the reproductive system of male rats. Reduction in body weight was indeed observed after sub-dermal exposure of Ag NPs in male rats when administered at a dose of 50 mg/kg BW for 28 days, whereas decrease in the relative weight of testes and epididymis was found with the same dose exposure for 7 days [ 65 ]. Therefore, it is evident that NPs’ impact on body and organ weight is dose and time dependent.…”
Section: Adverse Effects Of Nps On the Reproductive Systemmentioning
confidence: 99%